Mind–body training outperforms other physical activities in reducing frailty and enhancing quality of life in older adults: a network meta-analysis - Liu, Guangwen; Ge, Renkai; Zhu, Huiling (Frontiers in Public Health, 2025)
BackgroundPhysical activity is an effective strategy for treating and intervening in frailty syndrome, which leads to functional decline, increased hospitalization rates, and heightened mortality risks among older adult people. However, the relative effectiveness of different types of physical activity modalities in mitigating frailty and enhancing activities of daily living (ADLs) and quality of life (QoL) remains insufficiently explored. This network meta-analysis quantified and compared the effects of different physical activities on frailty, ADLs, and QoL, providing an evidence base for targeted interventions.MethodsFollowing the PRISMA-NMA guidelines, we conducted systematic searches of PubMed, Embase, and CNKI to identify 35 randomized controlled trials (N = 2,905) between January 2000 and August 2024. We employed the frequency science network meta-analysis model to quantify the relative efficacy of various physical activities in enhancing frailty management, ADLs, and QoL in older people.ResultsThe analysis revealed that Mind–body training (e.g., Taiji, Baduanjin), a traditional Chinese exercise that integrates gentle body movements with breath regulation, significantly alleviated debilitating conditions (SMD = −0.71, 95% CI: −1.22 to −0.21) and markedly improved quality of life (SMD = 1.02, 95% CI: 0.89 to 1.15). This modality proved to be the most effective of all the interventions studied. Aerobic training was particularly beneficial for enhancing the ability to perform ADLs (SMD = 0.89, 95% CI: 0.06 to 1.72). Although mixed physical activity exhibited overall efficacy across all health indicators (p < 0.05), its benefits did not exceed those of mind–body training. Further analysis indicated that the intervention regimen consisting of 50–60 min of training per session, 2–3 times per week, yielded the most significant improvements.ConclusionThis study employed network meta-analysis to compare the effects of various physical activities on frailty, ADLs, and QoL in older adults. The findings suggest that both mental and physical training significantly ameliorate frailty and enhance QoL, whereas aerobic training enhances daily living capabilities. Clinical interventions should prioritize tailored mental and physical training, considering individual differences. Future studies should focus on long-term effects and dose–response relationships to optimize frailty management and health promotion in older adult individuals.